PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN MEKARSARI KABUPATEN BARITO KUALA - Fahrul Zaini; Gerilyansyah Basrindu; Akhmad Abdurrahman (STIA Bina Banua Banjarmasin, 2019)
The Effect of Principal Leadership and Teacher Competence on Teachers' Performance in Public Elementary Schools in Mekarsari District, Barito Kuala Regency, Under the guidance of H. Gerilyansyah Basrindu, as the first supervisor and Akhmad Abdurahman, as the second supervisor. This study aims (1) to determine the effect of principals' leadership on the performance of state elementary school teachers in Mekarsari District, Barito Kuala Regency. (2) to find out the effect of teacher competency on the performance of state elementary school teachers in Mekarsari District, Barito Kuala Regency. The approach of this research is quantitative non-experimental. The population was all Public Elementary School teachers in Mekarsari Subdistrict with 86 teachers, and the sample size was determined by the Krejcie table of 65 people. The technique of collecting data using a questionnaire. Analysis of research results using descriptive statistics, simple regression, and multiple regression using SPSS Windows Version 21. Descriptively the results of the study point out that the leadership of principals in public elementary schools in MekarsariSubdistrict is included in the good category with an average score of 3.592, teacher competency in the excellent category with an average of 4.2594, teacher performance in the very good category with an average of 4.226. With simple regression analysis it is known: there is a significant influence of the principal's leadership on the performance of teachers at SD Negeri Mekarsari District at 29.0%, teacher competence has a significant effect on teacher performance with a coefficient of determination of 10.3%. Pengaruh Kepemimpinan Kepala Sekolah Dan Kompetensi Guru Terhadap Kinerja Guru Sekolah Dasar Negeri Di Kecamatan Mekarsari Kabupaten Barito Kuala, Dibawah bimbingan H. Gerilyansyah Basrindu, sebagai pembimbing Pertama serta Akhmad Abdurahman, sebagai pembimbing kedua. Penelitian ini bertujuan (1) untuk Mengetahui pengaruh kepemimpinan kepala sekolah terhadap kinerja guru Sekolah Dasar Negeri di Kecamatan Mekarsari Kabupaten Barito Kuala. (2) untuk Mengetahui pengaruh Kompetensi guru terhadap kinerja guru Sekolah Dasar Negeri di Kecamatan Mekarsari Kabupaten Barito Kuala. Pendekatan penelitian ini adalah kuantitatif non eksperimen. Populasi adalah seluruh guru Sekolah Dasar Negeri yang ada di Kecamatan Mekarsari dengan jumlah guru 86 orang, dan ukuran sampel ditentukan dengan tabel Krejcie sebanyak 65 orang. Teknik pengumpulan data dengan menggunakan angket. Analisis hasil penelitian menggunakan statistik deskriptif, regresi sederhana, dan regresi berganda dengan menggunakan SPSS Windows Version 21. Secara deskriptif hasil penelitian menujukan bahwa kepemimpinan kepala sekolah di SD Negeri di Kecamatan Mekarsari termasuk dalam kategori baik dengan skor rerata 3,592, kompetensi guru dalam kategori sangat baik dengan rerata 4,2594, kinerja guru masuk dalam kategori sangat baik dengan rerata 4,226. Dengan analisis regresi sederhana diketahui : terdapat pengaruh yang signifikan kepemimpinan kepala sekolah terhadap kinerja guru SD Negeri Kecamatan Mekarsari sebesar 29,0%, kompetensi guru berpengaruh signifikan terhadap kinerja guru dengan koefisien determinasi sebesar 10,3%.